2021
DOI: 10.3390/healthcare9040461
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Patients with Mental Disorders Default Treatment? A Qualitative Enquiry in Rural Kwazulu-Natal, South Africa

Abstract: Although treatment default by psychiatric patients or mental health care users is a global challenge, this behavior is reported to be higher in South Africa. The Manguzi District Hospital in rural Kwa-Zulu Natal Province, South Africa, experiences high rates of treatment default by psychiatric patients. The objective of this study was to determine the reasons for treatment defaulting at Manguzi Hospital, KwaZulu-Natal Province, South Africa. An explorative qualitative design, using in-depth interviews, was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The findings agree with [24], who found that family members often struggle to persuade MHCUs to take treatment as they have difficulty acknowledging that they are mentally ill. This was supported by a study conducted by [2], which highlighted that denial of mental health conditions and perceived cure is very much common among MHCUs who have poor health literacy regarding their condition, hence it results in poor health outcomes. Supervision of MHCUs is of particular concern because it affects the rate of early relapse after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The findings agree with [24], who found that family members often struggle to persuade MHCUs to take treatment as they have difficulty acknowledging that they are mentally ill. This was supported by a study conducted by [2], which highlighted that denial of mental health conditions and perceived cure is very much common among MHCUs who have poor health literacy regarding their condition, hence it results in poor health outcomes. Supervision of MHCUs is of particular concern because it affects the rate of early relapse after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 84%
“…Several factors were observed by the primary caregivers as the main reasons for MHCUs to redevelop psychiatric symptoms after being stabilised in hospitalisation. Although several studies have investigated factors associated with the occurrence of psychiatric symptoms after discharge, few studies have examined whether misconception about self mental health conditions is the cause of relapse among MHCUs [1,2,7,23]. Denial and perceived cure by MHCUs are the major barriers to complying with treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations